Une épistémologie du droit : L'État providence de François Ewald - Morissette, Yves-Marie (Les Cahiers de droit)

(untitled) (Faculté de droit de l’Université Laval, 1987)
When scholarly research in law confines itself to source materials, it effectively allows positive law to prescribe the limits of the intellectual enquiry. When it does not so confine itself, scholarly research gradually erases as it progresses the boundary between the object of its own enquiry and that of other disciplines in the human sciences. In the author's view, if ultimately law is to be seen as more than standardized common sense armed with a big stick, it must become responsive, from within, to the findings of these disciplines. But this process of integration raises serious methodological difficulties. Their solution, assuming there is one, will draw on epistemology and a reexamination of the relationship between law and knowledge. One recent and most commendable contribution to legal epistemology is François Ewald's L'Étatprovidence. The author, a philosopher, sets out to explain how the fundamental rationality of the French legal system was transformed at the beginning of the XXth century. Having first described the respective functions of law, morality and benevolence in the post revolutionary liberal model, Ewald then shows how probability theory made possible the development of statistics, modern sociology and « insurance technology ». The advent of a workmen's compensation scheme, a result of these developments, marked an epistemological breaking point French private law. From then onwards, the order of distributive justice never ceased to expand: risk became the rule and fault the exception. The change is now irreversible and the modern Welfare State has created its own original brand of justice. Michel Foucault's influence is often noticeable in L'État providence, a complex but fascinating book which illustrates why philosophy, legal scholarship and law, although capable of sharing certain outlooks, must forever remain distinct.